Parents’ Self Esteem of Children with Cleft Lip and Palate - Gadis Pratiwi Priyono; Imas Rafiyah; Ikeu Nurhidayah (Journal of Nursing Care, 2018)
Cleft lip and palate are congenital abnormalities that occur in children. Success in the management and treatment of this disorder requires the role of parents. However, often parents are embarrassed and have low self-esteem, so it would interfere with the success process of treatment and child care with clefts. This study aimed to determine the parents’ self-esteem of children with cleft lip and palate in the Yayasan Pembina Penderita Celah Bibir dan Langit-langit  (YPPCBL) Bandung. This research was a descriptive quantitative study. The study population was parents of children with cleft lip and palate. A total of 30 respondents participated in this study which was chosen with total sampling method. Parental self-esteem was measured using modified instruments based on Coopersmith's theory, with validity values of r = 0.977 and Cronbach's α = 0.989. Data were analyzed using frequency distribution. The results showed 18 respondents (60%) had high self esteem and 12 respondents (40%) with low self esteem. This research would be an evaluation material for YPPCBL Bandung in maintaining and improving parents' self-esteem of children having clefts. With high self-esteem, it is potential for nurses to increase parental participation as a primary caregiver of children with clefts, it would also improve the success of care and children’s quality of life.